Agrobacterium transformation of Rhodiola sp.: current status and limitations - Javid, A.; György, Zs. (International Journal of Horticultural Science, 2024)
The study of secondary metabolites has led to the discovery of new drugs for treating human diseases. However, consistent plant supply can be challenging, leading to the use of plant tissue culture techniques such as hairy root culture. Hairy roots have stable genetics, lateral branching, and can produce secondary metabolites, including alkaloids, flavonoids, and terpenoids. Research on hairy roots as a subject began in the late 19th century, and for the last four decades, hairy roots have been utilized for producing secondary metabolites and recombinant proteins. This article focuses on Rhodiola species - genus of perennial plants that belongs to the family Crassulaceae - and its potential as a source of secondary metabolites using hairy root culture techniques. Rhodiola sp. is widely distributed throughout the Arctic regions of the Northern Hemisphere, with several species having significant medicinal properties. The article discusses the possible use of hairy root cultures for the production of Rhodiola secondary metabolites, including salidroside and rosavins, which have demonstrated significant pharmacological activity in various studies. The use of elicitation and genetic engineering techniques to boost secondary metabolite production in Rhodiola hairy roots is also explored. Overall, the article highlights the potential of Rhodiola hairy root cultures as a valuable source of secondary metabolites with medicinal properties. However, despite some studies Rhodiola hairy root induction and culturing still remains highly unexplored.